EFFECT OF AEROBIC EXERCISE ON PHYSICAL FUNCTION INDICES IN THE ELDERLY - Mei,Nan (2023)
ABSTRACT Introduction China is currently experiencing the problem of population aging, and the health status of the elderly has become a major focus of social attention. Objective Study the effect of aerobic exercise on the indices of physical function in the elderly. Methods 40 elderly people performed aerobic exercise 5 times a week for 8 weeks. Each exercise lasted 60 minutes, including 10 minutes of warm-up, 40 minutes of aerobic exercise (running, brisk walking, square dancing, among other activities), and 10 minutes of final cool-down. Data measurement included body indices, cardiopulmonary function, blood markers, and exercise capacity. Results Aerobic exercise can effectively improve the body shape, cardiopulmonary function, and blood lipid content of the elderly, and improve their flexibility and physical quality, enhancing their activities of daily living. Conclusion The results of this study show that aerobic exercise can effectively improve the body performance of the elderly in activities of daily living, effectively optimizing cardiopulmonary and lipid indexes. Engaging the elderly to participate in aerobic exercise should be considered by community social workers. Level of evidence II; Therapeutic studies - investigation of treatment outcomes.